CRISPR/Cas9 editing of Nf1 gene identifies CRMP2 as a therapeutic target in neurofibromatosis type 1-related pain that is reversed by (S)-Lacosamide - Moutal, Aubin; Yang, Xiaofang; Li, Wennan; Gilbraith, Kerry B.; Luo, Shizhen; Cai, Song; Francois-Moutal, Liberty; Chew, Lindsey A.; Yeon, Seul Ki; Bellampalli, Shreya S.; Qu, Chaoling; Xie, Jennifer Y.; et al. (LIPPINCOTT WILLIAMS & WILKINS, 2017)
Neurofibromatosis type 1 (NF1) is a rare autosomal dominant disease linked to mutations of the Nf1 gene. Patients with NF1 commonly experience severe pain. Studies on mice with Nf1 haploinsufficiency have been instructive in identifying sensitization of ion channels as a possible cause underlying the heightened pain suffered by patients with NF1. However, behavioral assessments of Nf11/2 mice have led to uncertain conclusions about the potential causal role of Nf1 in pain. We used the clustered regularly interspaced short palindromic repeats (CRISPR)-associated 9 (CRISPR/Cas9) genome editing system to create and mechanistically characterize a novel rat model of NF1-related pain. Targeted intrathecal delivery of guide RNA/Cas9 nuclease plasmid in combination with a cationic polymer was used to generate allele-specific C-terminal truncation of neurofibromin, the protein encoded by the Nf1 gene. Rats with truncation of neurofibromin, showed increases in voltage-gated calcium (specifically N-type or CaV2.2) and voltage-gated sodium (particularly tetrodotoxin-sensitive) currents in dorsal root ganglion neurons. These gains-of-function resulted in increased nociceptor excitability and behavioral hyperalgesia. The cytosolic regulatory protein collapsin response mediator protein 2 (CRMP2) regulates activity of these channels, and also binds to the targeted C-terminus of neurofibromin in a tripartite complex, suggesting a possible mechanism underlying NF1 pain. Prevention of CRMP2 phosphorylation with (S)-lacosamide resulted in normalization of channel current densities, excitability, as well as of hyperalgesia following CRISPR/ Cas9 truncation of neurofibromin. These studies reveal the protein partners that drive NF1 pain and suggest that CRMP2 is a key target for therapeutic intervention.
Keywords: QUALITY-OF-LIFE; DORSAL-ROOT GANGLION; SENSORY NEURONS; NEUROPATHIC PAIN; HAPLOINSUFFICIENT MICE; CALCIUM-CHANNELS; PROTEIN; CAV2.2; PHOSPHORYLATION; MUTATION